2007
DOI: 10.1016/j.physrep.2007.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Glueballs, hybrids, multiquarks

Abstract: Glueballs, hybrids and multiquark states are predicted as bound states in models guided by quantum chromo dynamics (QCD), by QCD sum rules or QCD on a lattice. Estimates for the (scalar) glueball ground state are in the mass range from 1000 to 1800 MeV, followed by a tensor and a pseudoscalar glueball at higher mass. Experiments have reported evidence for an abundance of meson resonances with 0 −+ , 0 ++ and 2 ++ quantum numbers. In particular, the sector of scalar mesons is full of surprises starting from the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
736
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 840 publications
(763 citation statements)
references
References 1,110 publications
(1,165 reference statements)
24
736
0
3
Order By: Relevance
“…It is our understanding that this results partly from the fact that already at mesonic tree level there are signatures of quark-antiquark as well as of admixtures of 2 quark-2 antiquark states present, from the underlying multiquark Lagrangian, which contribute in the long distance asymptotics to the internal structure of the mesons as well as to the mesonic interaction terms. In many other approaches the more complex quark structures enter only through the explicit inclusion of meson loops, tetraquark configurations, and so on [66][67][68][69][70][71][72][73][74][75][76][77][78]. Table II shows the current and constituent quark masses in the isospin limit and the model parameters which do not break explicitly the chiral symmetry, the 4-quark coupling G, the 6-quark 't Hooft determinant coupling κ, and two 8-quark couplings g 1 , g 2 , of which g 1 is OZI-violating.…”
Section: Results and Further Discussionmentioning
confidence: 99%
“…It is our understanding that this results partly from the fact that already at mesonic tree level there are signatures of quark-antiquark as well as of admixtures of 2 quark-2 antiquark states present, from the underlying multiquark Lagrangian, which contribute in the long distance asymptotics to the internal structure of the mesons as well as to the mesonic interaction terms. In many other approaches the more complex quark structures enter only through the explicit inclusion of meson loops, tetraquark configurations, and so on [66][67][68][69][70][71][72][73][74][75][76][77][78]. Table II shows the current and constituent quark masses in the isospin limit and the model parameters which do not break explicitly the chiral symmetry, the 4-quark coupling G, the 6-quark 't Hooft determinant coupling κ, and two 8-quark couplings g 1 , g 2 , of which g 1 is OZI-violating.…”
Section: Results and Further Discussionmentioning
confidence: 99%
“…Interested readers may also consult reviews in Refs. [40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,39].…”
Section: General Status Of Hadron Spectroscopymentioning
confidence: 99%
“…An extensive review on spectroscopy in general can be found in reference [116], while a review focussing only on hybrid mesons is given in reference [117]. The experimental situation has evolved since these previous reviews, with new data from several experiments and detailed systematic studies of production mechanisms made possible by very-large data sets.…”
Section: Experimental Situationmentioning
confidence: 99%